THE IMPACT OF TECHNOLOGY AND TRANSFORMATIONAL LEADERSHIP OF HEAD OF SOKOSARI VILLAGE ON THE OPTIMIZATION OF SERVICE PERFORMANCE IN THE COMMUNITY - Moh. Heru Budi Santoso (Jurnal Scientia, 2023)
Humans play a dynamic role in institutional activities to realize the achievement of Institutional goals. Quality human resources can be seen from their educational background, training they have attended, skills stated in carrying out tasks and job descriptions. Developments in the digitalization era have had a very massive impact on performance an organization that is supported by existing technology, in addition to the role of leadership in the organization is an important factor determining the results to be achieved. Therefore, this study aims to determine the impact of the influence of technology and transformational leadership in increasing the performance of village organizations. In this study, a quantitative approach was used with the same number of population and respondents (saturated sampling). The tool used in the analysis was PLS SEM, with a questionnaire instrument. The results of the analysis obtained that the higher the technology controlled, the higher the performance produced. Likewise with technological relations. on transformational leadership, but the relationship between transformational leadership is not significant with performance.